The effectiveness of mindfulness-based cognitive therapy combined with medication therapy in preventing recurrence of major depressive disorder in convalescent patients - Guo, Hui-Rong; Wang, Jun-Ru; Wang, Ya-Li; Huang, Bai-Ling; Yang, Xu-Huan; Ren, Yu-Ming (Frontiers in Psychology, 2022)
Objective This study aims to investigate the effectiveness of mindfulness-based cognitive therapy (MBCT) combined with medication therapy in preventing the recurrence of major depressive disorder (MDD) in convalescent patients. Methods A total of 130 patients with convalescent MDD were enrolled in this prospective study. Sixty-five patients were assigned to the experimental group and received medication therapy combined with MBCT, and 65 patients were assigned to the control group and treated with medication alone. The recurrence rate and related hormonal changes were compared between the two groups. Results After 1 year of MBCT intervention, eight patients experienced recurrence in the experimental group, a recurrence rate of 12.31%, and 19 patients experienced recurrence in the control group, a recurrence rate of 29.23%. The Hamilton Depression Rating Scale (HAM-D) and the World Health Organization Quality of Life Scale (WHOQOL-BREF) scores in both the experimental and the control groups were significantly improved after treatment (P < 0.05). The difference in the HAM-D scores before and after treatment in the experimental group was 16.74 ± 4.54; this was significantly higher than that of the control group (8 ± 3.89, P < 0.0001). The WHOQOL-BREF scores in the experimental group were significantly improved compared with those of the control group (P < 0.0001). The differences in the levels of corticotrophin-releasing hormone (CRH), adrenocorticotropic hormone, and cortisol before and after treatment in the experimental group and the control group were statistically significant (P < 0.05). The difference in CRH before and after treatment in the experimental group was 16.8 ± 7.2, which was higher than that of the control group (2.75 ± 9.27, P < 0.0001). The intervention with MBCT had a significant impact on the recurrence of MDD [β = 1.206, P = 0.039, 95% (confidence interval) CI = 0.0790–1.229]. The difference in the HAM-D scores also had a significant impact on the recurrence of MDD (β = 1.121, P = 0.0014, 95% CI = 0.805–0.976). Conclusion Compared with medication therapy alone, the use of MBCT combined with medication therapy can effectively prevent the recurrence of MDD in convalescent patients.